2019
DOI: 10.1248/cpb.c19-00076
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microstructure of Granules Prepared by Continuous Twin Screw Granulator Using X-Ray Micro-computed Tomography

Abstract: Granules prepared by a continuous twin screw granulator (TSG) were analyzed by X-ray micro-computed tomography (X-ray μCT) and the relationships between porosity of granules and granule properties were investigated. A model formulation containing ibuprofen, lactose monohydrate, microcrystalline cellulose, and hydroxypropyl cellulose was used. The porosity of granules was measured by X-ray μCT and mercury porosimetry. The data sets obtained by both methods showed linear correlation despite different values, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A granule microstructure encompasses several properties such as porosity, surface morphology, component content uniformity, pore size distribution, open-to-closed pore ratio, etc. All these factors together affect the flow, strength, content uniformity, and stability of the granules [ 3 , 11 , 12 , 13 ] and also affect the critical quality attributes of downstream final dosage forms like tablets and capsules [ 7 , 14 , 15 , 16 ]. Studies have shown that variance in the porosity of the granules significantly affects the strength and dissolution of tablets [ 8 , 15 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A granule microstructure encompasses several properties such as porosity, surface morphology, component content uniformity, pore size distribution, open-to-closed pore ratio, etc. All these factors together affect the flow, strength, content uniformity, and stability of the granules [ 3 , 11 , 12 , 13 ] and also affect the critical quality attributes of downstream final dosage forms like tablets and capsules [ 7 , 14 , 15 , 16 ]. Studies have shown that variance in the porosity of the granules significantly affects the strength and dissolution of tablets [ 8 , 15 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous wet-granulation studies have been more focused on external structures and formation mechanisms (Emady et al, 2011(Emady et al, , 2013Gao et al, 2018Gao et al, , 2020Iveson et al, 2001;Li et al, 2019Li et al, , 2021. There have been lab-based micro-CT studies on granule internal structures, but these have focused on the final granule product and not on in situ granulation (Crean et al, 2010;Davis et al, 2017;Farber et al, 2003;Matsui et al, 2019). The X-ray flux from lab-based scanners is not sufficient to capture in situ wet granulation (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%